Local IL-17A potentiates early neutrophil recruitment to the respiratory tract during severe RSV infection. - Arie Jan Stoppelenburg; Vahid Salimi; Marije Hennus; Maud Plantinga; Ron Huis in 't Veld; Jona Walk; Jenny Meerding; Frank Coenjaerts; Louis Bont; Marianne Boes (PLoS ONE, 2013)
Respiratory syncytial virus (RSV) bronchiolitis triggers a strong innate immune response characterized by excessive neutrophil infiltration which contributes to RSV induced pathology. The cytokine IL-17A enhances neutrophil infiltration into virus infected lungs. IL-17A is however best known as an effector of adaptive immune responses. The role of IL-17A in early immune modulation in RSV infection is unknown. We aimed to elucidate whether local IL-17A facilitates the innate neutrophil infiltration into RSV infected lungs prior to adaptive immunity. To this end, we studied IL-17A production in newborns that were hospitalized for severe RSV bronchiolitis. In tracheal aspirates we measured IL-17A concentration and neutrophil counts. We utilized cultured human epithelial cells to test if IL-17A regulates RSV infection-induced IL-8 release as mediator of neutrophil recruitment. In mice we investigated the cell types that are responsible for early innate IL-17A production during RSV infection. Using IL-17A neutralizing antibodies we tested if IL-17A is responsible for innate neutrophil infiltration in mice. Our data show that increased IL-17A production in newborn RSV patient lungs correlates with subsequent neutrophil counts recruited to the lungs. IL-17A potentiates RSV-induced production of the neutrophil-attracting chemokine IL-8 by airway epithelial cells in vitro. Various lung-resident lymphocytes produced IL-17A during early RSV infection in Balb/c mice, of which a local population of CD4 T cells stood out as the predominant RSV-induced cell type. By removing IL-17A during early RSV infection in mice we showed that IL-17A is responsible for enhanced innate neutrophil infiltration in vivo. Using patient material, in vitro studies, and an animal model of RSV infection, we thus show that early local IL-17A production in the airways during RSV bronchiolitis facilitates neutrophil recruitment with pathologic consequences to infant lungs.